2012
DOI: 10.1158/1078-0432.ccr-11-2034
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of a Novel Subset of CD8+CD57+ T Cells in Metastatic Melanoma with an Incompletely Differentiated Phenotype

Abstract: PURPOSE Tumor-specific T-cells are frequently induced naturally in melanoma patients and infiltrate tumors. It is enigmatic why these patients fail to experience tumor regression. Given that CD8+ T cells mediate antigen-specific killing of tumor cells, the focus of this study was to identify alterations in the differentiation of CD8+ residing at the tumor site, with emphasis on a population expressing CD57, a marker for terminal differentiation. EXPERIMENTAL DESIGN We performed flow cytometric analysis of CD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
(90 reference statements)
1
14
0
2
Order By: Relevance
“…Upregulation of CD57 is normally interpreted as continued progression to a terminally differentiated phenotype (30). The population of CD27 þ CD57 þ cells that we described here is unusual but has been described previously in patients with melanoma (31).…”
Section: Discussionsupporting
confidence: 71%
“…Upregulation of CD57 is normally interpreted as continued progression to a terminally differentiated phenotype (30). The population of CD27 þ CD57 þ cells that we described here is unusual but has been described previously in patients with melanoma (31).…”
Section: Discussionsupporting
confidence: 71%
“…From these experiments, we concluded that CD57 upregulation on the CAR T cells upon encounter with the GBM-SCs did not reflect a terminally differentiated T cell state. CD57 upregulation on CD27+ T cells has recently been linked to a state of incomplete differentiation of tumor-infiltrating T cells (TILs), which, in contrast to terminally differentiated T cells, are still able to proliferate upon TCR stimulation but rapidly undergo terminal differentiation (indicated by the downregulation of CD27 and CD28 and the upregulation of perforin) upon further antigen stimulation [ 33 ]. After incubation with NCH421k GBM-SCs and subsequent upregulation of CD57, our AC133-specific CAR T cells still proliferated when further cultured on anti-CD3 antibody-coated plates or with AC133+ NCH421k GBM-SCs for several days and they downregulated neither CD27 nor CD28 (data not shown), suggesting that the strong CD57 upregulation on the CAR T cells upon incubation with GBM-SCs did not reflect terminal replicative senescence, nor was it identical to the state of incomplete T cell differentiation recently described by Wu et al .…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al . [14] recently described a subpopulation of melanoma-specific CD8+ tumor-infiltrating lymphocytes (TILs) with hybrid phenotypic and functional properties of both an early effector-memory cell and a terminally differentiated effector cell co-expressing CD27, CD28, and CD57. These CD57+ T cells were classified as incompletely differentiated T cells.…”
Section: Introductionmentioning
confidence: 99%